Does muscle-tendon unit structure predispose to hamstring strain injury during running? A critical review - Huygaerts, S.; Cos, F.; Cohen, D. D.; Calleja-Gonzalez, J.; Pruna, R.; Alcaraz, P. E.; Blazevich, A. J. (Sports Medicine, 2021)
Hamstring strain injury (HSI) remains the most common muscle injury in high-intensity running in humans. The majority of acute HSI occur specifically within the proximal region of the long head of biceps femoris and there is a sustained interest among researchers in understanding the factors that predispose to HSI. The present critical review describes the current understanding of biceps femoris long head (BFlh) structural features that might influence strain injury risk. Inter-individual differences in muscle-tendon architecture and interactions, muscle fiber type and region-specific innervation are likely to influence biceps femoris long head injury risk and might inform why some individuals are at an increased risk of sustaining a HSI during running. However, more research is needed, with future studies focusing on prospective data acquisition, improved computer simulations and direct imaging techniques to better understand the relationship between structural features, hamstring muscle function, and injury risk.